The Influence Corporate Governance and Financial Distress on Tax Avoidance - Salsabilla, Raden Rara Adinda; Sulistyowati; Husen, Irfan; Zulkarnaini, Zulkarnaini (Santoso Academy Network, 2023)
This study aims to test the effect of corporate governance proxied by institutional ownership, independent board of commissioner, and audit committee and the effect of financial distress on tax avoidance in infrastructure, transportation, and logistics companies. This research uses a descriptive quantitative approach, which is analyzed using linear regression analysis of panel data such as the Chow test, Hausman test, classic assumption test, and hypothesis testing using EViews version 12 software. The population in this study is infrastructure, transportation, and logistic companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample of this study is 24 companies that were determined by purposive sampling method so that 120 observations were obtained. The results of this study partially show that Corporate Governance, which is proxied by Institutional Ownership, Independent Board of Commissioners, and Audit Committee, has no significant effect on Tax Avoidance, and Financial Distress has a significantly negative effect on Tax Avoidance in infrastructure, transportation, and logistic.